Topotactic Conversion of β‐Helix‐Layered Silicate into AST‐Type Zeolite through Successive Interlayer Modifications. Issue 7 (15th January 2014) - Asakura, Yusuke; Takayama, Ryosuke; Shibue, Toshimichi; Kuroda, Kazuyuki
Abstract AST‐type zeolite with a plate morphology can be synthesized by topotactic conversion of a layered silicate (β‐helix‐layered silicate; HLS) by using N, N‐dimethylpropionamide (DPA) to control the layer stacking of silicate layers and the subsequent interlayer condensation. Treatment of HLS twice with 1) hydrochloric acid/ethanol and 2) dimethylsulfoxide (DMSO) are needed to remove interlayer hydrated Na ions and tetramethylammonium (TMA) ions in intralayer cup‐like cavities (intracavity TMA ions), both of which are introduced during the preparation of HLS. The utilization of an amide molecule is effective for the control of the stacking sequence of silicate layers. This method could be applicable to various layered silicates that cannot be topotactically converted into three‐dimensional networks by simple interlayer condensation by judicious choice of amide molecules.